DESIGN AND DEVELOPMENT OF USABLE FURNITURE FOR DEWAN SERBAGUNA IN TAMAN SAMARINDAH COMMUNITY - Mohd Azrin, Mohd Said; Mohamad Syazwan Zafwan, Mohamad Suffian; Rasli, Muslimen; Aaron Edward Sheng, Jye Teo (2025)
This service-learning project aimed to empower students to contribute to community development by addressing fundamental needs, strengthening their technical and interpersonal skills, fostering a sense of civic responsibility, and ultimately promoting sustainable social impact through education. By guiding students through the whole engineering design cycle from community consultation to final implementation the project helped them reframe their roles as future engineers who innovate not only for industry but also for society. It provided a transformative platform where academic learning was directly applied to real-world challenges, allowing students to witness the tangible outcomes of their work. This initiative also demonstrated how university-community collaboration can serve as a powerful driver for inclusive development and experiential learning excellence.